The Assessment of Science Process Skills in Biology Subject Lesson Plan Sheets - Nur Fatrah Pakaya; Lilan Dama; Mustamin Ibrahim (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to find out the science process skills on the lesson plans for biology at SMA Negeri 1 Gorontalo. This research is a qualitative descriptive study to determine the existence of aspects of science process skills in lesson plans. This research data collection technique uses observation sheets and in-depth interviews. Data analysis includes data reduction, data presentation, drawing conclusions, and testing the validity of the data using the triangulation method. The primary data in this study were biology teachers in class XI, and the secondary data was obtained from notes or documentation in the form of odd semester biology lesson plans for class XI. The results of the study show that in the entire lesson plan which consists of 21 meetings, there are 3 formulations of science process skills in it, namely; observing skills, asking questions, and communicating skills. Other science process skills were obtained based on the results of the interviews conducted, namely classifying skills on the material of cells meeting 2, material of cells meeting 3, material on the structure and function of bones meeting 1, material on the structure and function of tissues in animals meeting 1, material on the structure and function of tissues on plants meeting 1, material on the structure and function of cells in the digestive system meeting 1, material on the structure and function of cells in the digestive system meeting 3, as well as material on the structure and function of the circulatory system meeting 1. Meanwhile, for all the science process skills studied lies in material membrane transport and nutrient assay.